Maternal Knowledge of the “Birth Planning and Complication Prevention Program” as a Determinant of Postpartum Contraceptive Decision Making - Serlyansie V Boimau; Tirza Vivianri Isabela Tabelak; Matje Meriaty Huru; Agustina Ningsi; Zulaeha A Amdadi; Agustina Abuk Seran; Adriana M S Boimau (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Serlyansie V Boimau1, Tirza Vivianri Isabela Tabelak1, Matje Meriaty Huru1, Agustina Ningsi2, Zulaeha A Amdadi2, Agustina Abuk Seran1, Adriana M S Boimau1 1, Indonesia; 2Midwifery Department, Poltekkes Kemenkes Makassar, Makassar, Indonesia Correspondence: Serlyansie V Boimau: Jl. R.A. Kartini, Kelapa Lima, Kupang, Indonesia; serlyansieboimau69@gmail.com ABSTRACT Rapid population growth remains a major demographic challenge in Indonesia, driven by limited reproductive health knowledge and persistent cultural norms. To support population regulation and improve maternal health, the government promotes the Family Planning Program, making it essential to understand factors that shape women’s decisions regarding postpartum contraception. This study aimed to examine the relationship between maternal knowledge of the Birth Planning and Complication Prevention Program and decision making about postpartum contraceptive use in the working area of the Tarus Community Health Center in Kupang District, East Nusa Tenggara. An analytic survey with a cross sectional approach was conducted among thirty pregnant women attending five community health posts, using a structured questionnaire and applying descriptive statistics and the Chi Square test for analysis. The findings indicate that most respondents demonstrated good knowledge of the Birth Planning and Complication Prevention Program and that the majority decided to use postpartum contraception. A statistically significant association was identified between maternal knowledge of the program and postpartum contraceptive decision making. These results suggest that stronger understanding of birth planning and complication prevention encourages informed choices regarding postpartum contraception, underscoring the importance of enhanced educational efforts for pregnant women. Keywords: maternal knowledge; birth planning; complication prevention; decision making; postpartum contraception